The Level Of Sharia Financial Literacy Among Muhammadiyah Members In Bulukumba Regency, South Sulawesi Indonesia - Andi Paradiba Tenri Awaruh; Agusdiwana Suarni; Abdul Khaliq; Nur Fitri Amaliah; Sahabuddin N (IECON: International Economics and Business Conference, 2024)
This study aims to assess the level of Islamic financial literacy among Muhammadiyah members in Bulukumba Regency. A quantitative approach was used with observation, questionnaire, and documentation methods, as well as descriptive analysis for data interpretation. The population of this study was Muhammadiyah members aged 15-69 years, with a sample of 91 people calculated using the Slovin formula. The results showed that the level of Islamic financial literacy among Muhammadiyah members in Bulukumba Re gency was 73.04%, which indicates a moderate category (60% - 79%). The scores for each indicator are as follows: Islamic economics (84.22%), basic knowledge of Islamic finance (73.18%), Islamic savings and loans (70.94%), Islamic insurance (70.91%), and Islamic investment (68.22%).